Havoc of Papaya Mealybug (Paracoccus marginatus) and Its Management Strategies - Dipti Joshi (International Journal of Insects, 2025)
The papaya mealybug (Paracoccus marginatus) is a serious problem that affects mulberries, citrus, and papaya among other agricultural and horticultural crops. Originating in Central America, it has spread around the world and caused extensive harm because of its capacity to consume plant sap, which results in reduced crop yields, fruit drop, and chlorosis. In addition, the insect releases honeydew, which encourages the development of sooty mold, further impeding photosynthesis and lowering the quality of fruit. Reducing its economic impact requires the use of effective management measures. The successful application of Integrated Pest Management (IPM) techniques combines cultural customs, the prudent use of chemical pesticides, and biological control agents like parasitoids (like Acerophagus papayae). Biological management has shown a lot of promise for long-term pest population suppression, reducing crop residue from chemicals, and fostering environmental sustainability. Creating control plans tailored to a given location requires a thorough understanding of the biology, ecology, and spread of the pest. Environmentally friendly techniques and biological agents are the focus of natural control strategies. Because parasitoid wasps lay their eggs within mealybugs and subsequently kill them, using wasps like Acerophagus papayae, Anagyrus loecki, and Pseudleptomastix mexicana is a highly successful method. Mealybug populations are also decreased by entomopathogenic fungi like Beauveria bassiana and Lecanicillium lecanii, as well as predatory beetles like Cryptolaemus montrouzieri, also known as the “mealybug destroyer”. Insecticides that are botanical, like pyrethrum and neem oil, provide a natural substitute by stopping insects from feeding and reproducing, and cultural methods like keeping fields clean, managing ants, and examining plants can stop pests from spreading. To help with pest control, physical techniques like high-pressure water sprays can be used to remove mealybugs from plants. These strategies have proved to be beneficial in terms of management for papaya mealybug and has better opportunities in the coming future.
Keywords: Agriculture; Paracoccus marginatus; horticulture; integrated pest management; mealybug